Carbon dioxide evaporation in a single microchannel - Gasche, José L. [UNESP] (Springer Nature, 2006)
Despite its importance for designing evaporators and condensers, a review of the literature shows that heat transfer data during phase change of carbon dioxide is very limited, mainly for microchannel flows. In order to give a contribution on this subject, an experimental study of CO 2 evaporation inside a 0.8 mm-hydraulic diameter microchannel was performed in this work. The average heat transfer coefficient along the microchannel was measured and visualization of the flow patterns was conducted. A total of 67 tests were performed at saturation temperature of 23.3°C for a heat flux of 1800 W/(m2°C). Vapor qualities ranged from 0.005 to 0.88 and mass flux ranged from 58 to 235 kg/(m2s). An average heat transfer coefficient of 9700 W/(m2°C) with a standard deviation of 35% was obtained. Nucleate boiling was found to characterize the flow regime for the test conditions. The dryout of the flow, characterized by the sudden reduction in the heat transfer coefficient, was identified at vapor qualities around 0.85. Flow visualization results showed three flow patterns. For low vapor qualities (up to about 0.25), plug flow was predominant, while slug flow occurred at moderated vapor qualities (from about 0.25 to 0.50). Annular flow was the flow pattern for higher vapor qualities. Copyright © 2006 by ABCM.
Keywords: Carbon dioxide; Evaporation; Flow pattern; Heat transfer coefficient; Microchannel; Mass flux; Microchannels; Saturation temperature; Vapor qualities; Evaporators; Flow patterns; Heat transfer; Heat transfer coefficients; Nucleate boiling